Endoscopic Intramural Surgery Part II: Muscular Division - Barajas-Gamboa, Juan S.; Corcelles, Ricard; Kroh, Matthew (Digestive Disease Interventions, 2018)
The development of endoscopic technologies and the introduction of new surgical concepts during the last decade has led to an evolution of surgical treatment of gastrointestinal disorders including achalasia, gastroesophageal reflux, gastroparesis, inflammatory bowel disease, and tumors of the gastrointestinal tract. Intramural surgery creates a novel approach to perform muscular division, submucosal dissection, and tumor removal. These procedures have proven safe and effective, and increasingly are part of the surgical endoscopist's toolbox. Intramural surgical procedures include peroral esophagomyotomy (POEM), peroral pyloromyotomy (POP), Zenker's diverticulotomy, and submucosal tunneling and endoscopic resection (STER) of lesions. The objective of this article is to describe current intramural surgery procedures that comprise muscular division, as well as clinical outcomes and its impact on surgical endoscopic practices.
Keywords: gastrointestinal disorders; intramural surgery; endoscopic surgery; NOTES; minimally invasive surgery